Effect of Thyme Leaves Extract on Quality of Lamb and Chicken Meat during Storage. - Baker, Ibrahim A.; Oray, Khalil A.D.; Hussein, Khabat N. (Science Journal of University of Zakho, 2015)
It has been known that thyme have antioxidant capacity and antimicrobial activity against different bacteria, therefore this investigation was designed to study the effect of adding thyme extract (0, 250, 500 and 1000 ppm) on the oxidative rancidity and microbial growth on lamb and chicken patties stored at 4C° for 12 days. The result revealed that malondialdehyde (MDA) values started to increase during storage periods, of both lamb and chicken patties. Extract of thyme apparently retarded significantly (p<0.01) oxidative rancidity and microbial growth as well in both lamb and chicken patties. Thus it can be concluded that addition of thyme especially at a rate of 500 ppm is effective as compared to untreated patties against oxidation and microbial growth.